2004
DOI: 10.1079/bjn20031066
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive potential of male Portan rats exposed to various levels of lead with regard to zinc status

Abstract: The present study was designed to elucidate the mechanisms accounting for disruption of the normal function of the testis exposed to various levels of Pb. Three different doses of Pb (10, 50, 200 mg Pb/kg body weight per d) were given orally to male Portan rats (groups 2, 3, 4). Zn (1 mg Zn/kg body weight per d) was also given with Pb (50 mg Pb/kg body weight per d) in group 5. Treatments continued for 3 months. Plasma luteinizing hormone and follicle-stimulating hormone concentrations were found to be decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
(27 reference statements)
0
24
0
1
Order By: Relevance
“…In cell kinetic studies, significant declines in various cell populations, spermatids and mature spermatozoa were detected. [27] It has been shown that lead is able to induce lipid peroxidation, one of the main manifestations of oxidative stress. [28] As compared with the controls, the lead-exposed group of rats showed alteration of the histopathologic pattern and reduction in the size of seminiferous tubules, basal membrane separation and a decrease in the cell content of the germinal layer, lesions of the spermatocytes and spermatids, and slight oedematous dissociation in the interstitium similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…In cell kinetic studies, significant declines in various cell populations, spermatids and mature spermatozoa were detected. [27] It has been shown that lead is able to induce lipid peroxidation, one of the main manifestations of oxidative stress. [28] As compared with the controls, the lead-exposed group of rats showed alteration of the histopathologic pattern and reduction in the size of seminiferous tubules, basal membrane separation and a decrease in the cell content of the germinal layer, lesions of the spermatocytes and spermatids, and slight oedematous dissociation in the interstitium similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Egypt. Nephrotoxicity was induced by giving rats lead acetate dissolved in distilled water at dose 50 mg/kg body weight/ day by gastric tube [20].…”
Section: Induction Of Nephrotoxicitymentioning
confidence: 99%
“…Unlike Zn and Ge, Pb is not beneficial to health. Pb can result in neurologic [61,62,63], skeletal, reproductive [64,65], hematopoietic [66,67], and urinary system [68,69] toxicity.…”
Section: Introductionmentioning
confidence: 99%